Analysis of first degree polynomial function teaching strategies to social applied sciences courses - Antunes, Daniele Mendes Caldas; Poffal, Cristiana Andrade; Rodriguez, Bárbara Denicol do Amaral; Sperotto, Fabíola Aiub (Ciência e Natura, 2018)
This paper aims present a study on the students’ ability to perform relations between first degree polynomial functions (domain, the range, x-intercept and y-intercept) and the economic theory which involves income, cost and revenue, practical applications in the professional area. The proposed study analyses the application of two practical activities containing real data of companies of the textile field. They require math and economical knowledge, reading and comprehension of data and results. This research was conducted at Universidade Federal do Rio Grande, RS, Brazil, in a group from the second semester of Business Administration Course.